Genomic language models could transform medicine but not yet - Micaela Elisa Consens; Ben Li; Anna R. Poetsch; Stephen Gilbert (npj Digital Medicine)
Recently, a genomic language model (gLM) with 40 billion parameters known as Evo2 has reached the same scale as the most powerful text large language models (LLMs). gLMs have been emerging as powerful tools to decode DNA sequences over the last five years. This article examines the emergence of gLMs and highlights Evo2 as a milestone in genomic language modeling, assessing both the scientific promise of gLMs and the practical challenges facing their implementation in medicine.